Optimasi Air Perasan Buah Merah (Pandanus sp.) Pada Pemeriksaan Telur Cacing - Oktari, Anita; Mu’tamir, Ahmad (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Worm infections or can be called by worming included into an infection caused by a parasite. Soil Transmitted Helminths Intestinal Nematodes are worms groups are in their life cycle to reach the infective stage requires soil with certain conditions. Eosin 2% is the dye that is used in the examination of Intestinal Nematode worm eggs. Red fruit (Pandanus sp.) which is a natural plant material and acidic contain carotenoids which produces orange-red pigment. Beta carotene is the predominant pigment of red-orange color that is found naturally in plants and fruits. The aim of this research is to determine the best concentration from variation of red fruit (Pandanus sp.) juice that optimally to color the eggs of the worm. Research conducted experiments with various concentration ratio of red fruit (Pandanus sp.) juice and distilled water (1, 1:1, 1:2, 1:3, 1:4, 1:5). From this research it found that the results indicate the ratio of concentrations of red fruit (Pandanus sp.) juice and distilled water (1:2) can be used as an alternative reagent eosin 2% for their examination of worm eggs. But in the visual field that uses red fruit (Pandanus sp.) juice and distilled water (1:2) still looks much dirt as a nuisance and does not give a contrasting background. It can conclude that red fruit (Pandanus sp.) juice can use to color the eggs of the worm.